Healthcare Workers' Resilience Mediates the Influence of Organizational Commitment and Anxiety Response to Viral Epidemic on Their Quality of Life in the COVID-19 Pandemic - Son, Hoon Sung; Kim, Kyumin; Cho, Inn-Kyu; Lee, Joohee; Choi, Jung Mun; Kil, Kwang Hyun; Kim, Jiyeon; Hong, Youjin; Ahn, Myung Hee; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Abstract Objective In the COVID-19 pandemic era, healthcare workers suffer from psychological problems such as anxiety in response to the viral epidemic and it may decrease their quality of life (QoL). The aim of this study was to explore the influence of healthcare workers’ stress and anxiety response to the viral epidemic and their organizational commitment on their QoL. We also explored the mediating effect of resilience on any association. Methods From January 28, 2021, to January 29, 2021, 389 workers responded to an online survey that included the rating scales Stress and Anxiety to Viral Epidemic-9 items (SAVE-9), Perceived Stress Scale (PSS), Brief Resilience Scale (BRS), Organizational Commitment Questionnaire (OCQ), and the WHO-5 well-being index. Results A better QoL (WHO well-being index top 25%) of healthcare workers during the COVID-19 pandemic era was predicted by low stress and anxiety in response to the viral epidemic (SAVE-9, adjusted odds ratio [aOR]=0.92, 95% confidence interval [CI] 0.87‒0.97), a high level of resilience (BRS, aOR=1.26, 95%CI 1.15‒1.37), and high organizational commitment (OCQ, aOR=1.04, 95%CI 1.02‒1.07). Mediation analysis showed that resilience partially mediated the effects of stress/anxiety in response to the viral epidemic and the organizational commitment on the quality of life. Conclusion We observed that the stress and anxiety of healthcare workers in response to the viral epidemic and organizational commitment influenced their QOL. Their resilience mediated the relationship between their psychological problems and QOL.